2000
DOI: 10.1007/s004250050676
|View full text |Cite
|
Sign up to set email alerts
|

Late steps of egg cell differentiation are accelerated by pollination in Zea mays L.

Abstract: Egg cells were analysed cytologically during the female receptivity period in maize (Zea mays L., line A 188). Three classes of egg cell were distinguished: type A--small, non-vacuolated cells with a central nucleus; type B--larger cells with small vacuoles surrounding the perinuclear cytoplasm located in the middle of the cell; type C--big cells with a large apical vacuole and the mid-basal perinuclear cytoplasm. The less-dense cytoplasm of the vacuolated egg cells usually contained numerous cup- or bell-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Mól et al (2000) reported that egg cell maturation is essentially accelerated after pollination in maize, but removal of silk directly after pollination did not repress accelerated egg maturation, suggesting an electric nature of the pollen signal. Even wounding using sea sand is able to promote egg maturation (R. Mól, personal communication), indicating the potential existence of long-range signals unrelated to peptides/ proteins.…”
Section: Cross-talk Between Gametesmentioning
confidence: 96%
“…Mól et al (2000) reported that egg cell maturation is essentially accelerated after pollination in maize, but removal of silk directly after pollination did not repress accelerated egg maturation, suggesting an electric nature of the pollen signal. Even wounding using sea sand is able to promote egg maturation (R. Mól, personal communication), indicating the potential existence of long-range signals unrelated to peptides/ proteins.…”
Section: Cross-talk Between Gametesmentioning
confidence: 96%
“…If pollination is withheld, S-phase in the egg cell is completed at 84 h, which is more than a 1-day delay; thus, pollination may accelerate cell cycle progression in the egg cell. In maize, maturation of the female gamete also is accelerated by several hours with the presence of pollen tubes in the style (Mó l et al, 2000).…”
Section: Long-distance Cues Promoting Gamete Maturation and Synchronymentioning
confidence: 99%
“…Polyspermy is reportedly blocked successfully, and chemical signals, including a calcium influx, have been recorded (see Calcium Waves, Site of Fusion, and Egg Activation below). The model seems to work best on slightly immature egg cells (Mó l et al, 2000) and is a bit technically demanding because receptivity may decline quickly after isolation. However, this model system does not seem to predict all types of gametic behavior.…”
Section: In Vitro Studies Of Fertilization In Flowering Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is supposed that the pollen-stigma interaction initiates this process. In some species (in Zea mays L.), pollination with pollen of the same species accelerates maturation and changes in the structure of egg cells (Mól et al, 2000). Moreover, during compatible or incompatible pollination, pollen tubes ( and papillae on the stigma sur-face) release a higher concentration of calcium ions Ca 2+ , which allows their penetration through the transmission tissue into the style (Śnieżko and Winiarczyk, 1993;Lenartowska et al, 2001).…”
Section: Discussionmentioning
confidence: 99%